ANALISIS PENTINGNYA PENGEMBANGAN MODUL BERBASIS VIDEO ASSISTANT MENGGUNAKAN LINK QR CODE TENTEGRASI ALQURAN DAN HADIS MATERI SMA SISTEM REPRODUKSI MANUSIA - Hafis Kaunang Ataji; Agus Sutanto (Universitas Muhammadiyah Metro, 2020)
Abstract: The development of this module is based on the learning process that already uses internet media, but in reality its use during the learning process has not been maximized and the use of the internet for learning has not been able to direct students to achieve learning objectives, the need for learning videos to facilitate students' understanding and integration of the Koran and Hadith into learning process. The purpose of writing this article is to produce an analysis in the form of assistant video based using QR Code links with Alquran and Hadis tentegration in materials of human reproduction systems, class XI, is it important and worth developing. This development research uses the Thiagarajan model in 1974 which only took 3 stages namely define, design, and develop. Based on the analysis results obtained observation results through the process of interviewing biology subject teachers at SMA N 1 Punggur are as follows, the learning process has implemented the internet in assignments, has never developed an electronic media-based module, and the results of student analysis, all students already have mobile phones. Based on the results of interviews and observations made it is necessary to develop the module.